Crude oil shocks and stock returns in African stock markets. - Enwereuzoh, Precious Adaku (My University, 2019)
Considering that Africa’s energy consumption per capita is growing faster than those of most continents in the world, driven by improved infrastructure and inflow of investment which have made Africa a major player in the international oil market, the need to study the impact of changes in oil prices on the stock market is of great importance. The stock Market is important as it acts as an economic barometer and reflects activities in the economy. The study investigates the impact of crude oil shocks on selected African stock markets. The countries selected are classified into two; with Nigeria, Tunisia, and Egypt as net oil-exporters, and Botswana, South Africa, Kenya, and Mauritius as Oil-importers. Using a Structural Vector Autoregressive model and a two-state regime Markov-switching framework, the study analyzed the impact of crude oil shocks on real stock returns over the period January 2000 to July 2018 at monthly frequency. Empirical findings from the study suggest that oil supply shock is statistically insignificant for most countries with the exception of Kenya; oil demand shock is positive in at least one regime for all countries and oil specific shock is statistically significant for oil-exporters with Nigeria having a negative impact on their stock returns, Tunisia having a negative and positive impact at different regime and a positive impact for Egypt. For oil-importers, oil specific shock has a positive impact on the stock returns of all countries except for Kenya. The findings from this study has important implications for investors whose portfolio may comprise of asset from African stock markets and crude oil. Given the phenomenal importance of oil in the global market one would typically avoid equities that suffer from its shock. This study provides the indicators to inform that decision.
MASTER OF MANAGEMENT IN FINANCE AND INVESTMENTS A RESEARCH REPORT Wits Business School University of the Witwatersrand Johannesburg, South Africa April 2019
Keywords: Stocks--Prices--South Africa; Petroleum products--Prices